Improving the Quality of Life of Orphans through a Religious Approach and Assistance in RW 10 Semanan, Kali Deres District, West Jakarta, in Collaboration with LBH–Pikiran dan Jiwa Rakyat - Miptahhudin; M. Riza Dzul Fahmi Aly (IRDH International Journal of Social Sciences & Humanities, 2025)
Orphans are a socially and psychologically vulnerable group due to the loss of their parents, who are key figures in their lives. In the Islamic context, orphans receive special attention and have rights that must be upheld by society. This article discusses the role of a religious approach in improving the quality of life of orphans, both spiritually, morally, and socially. Through religious education, moral development, and the practice of worship, orphans are guided to develop strong personalities, self-confidence, and a clear sense of direction in life. A religious approach also functions as psychological therapy, fostering optimism and resilience in the face of life's pressures. Studies show that consistent spiritual development can empower orphans to become individuals with noble character, independence, and a strong zest for life. Therefore, the integration of religious education and social support is a crucial strategy for holistically improving the lives of orphans. The lives of orphans are often characterized by limitations, both economically, socially, and psychologically. Therefore, the active role of the community and social institutions is needed to support them through a comprehensive approach. This article discusses the orphan assistance program in the RW 10 Semanan area, organized in collaboration with the Legal Aid Institute – Pikiran dan Jiwa Rakyat (LBH-PIJAR). A religious approach is prioritized as a foundation for moral and spiritual development, while material assistance is provided to support the children's well-being. This program is expected to improve the quality of life of orphans and foster social awareness in the surrounding community. Assistance for orphans is a form of social care that has a significant impact on their well-being and development.